Kualitas Hidup Pasien Lansia dengan Nyeri Punggung Bawah di Rumah Sakit Umum Ulin Banjarmasin: Penelitian - Rumboko, Raihan Febri; Noor, Zairin; Nurikhwan, Pandji Winata; Putera, Husna Dharma; Panghiyangani, Roselina (PT Kalbe Farma Tbk., 2025)
Introduction: Low back pain can change the daily life and quality of life of the elderly. This study aims to determine the quality of life of elderly patients with and without low back pain at Ulin General Hospital Banjarmasin. Methods: This study used an analytical observational approach with a cross‑sectional design. Sampling was through a purposive sampling approach according to the inclusion criteria. The study population was 100 patients aged 60 and over, half of the population with low back pain. The Indonesian versions of the WHOQoL‑BREF and SF‑36 questionnaires were used as a research instrument. Results: The results showed significant differences in the quality of life in the elderly patients with low back pain in 4 domains, namely physical functioning (p = 0.006), role limitations due to physical health (p = 0.023), social functioning (p = 0.009), and general health (p < 0.001), with median of each domain in order are 62,5 (0–100), 50 (0–100), 75 (0–100), and 50 (4–100). No significant differences in other domains in the WHOQoL-BREF and SF-36 questionnaire. Conclusion: Low back pain affects the life of elderly patients at Ulin General Hospital Banjarmasin, which was different in 4 aspects, namely physical functioning, role limitations due to physical health, social functioning, and general health.